Complexity of Boko Haram Insurgency: A Reflection on Ebira Tao North Central of Nigeria, 2003-2013 - Abedo, Abdussalam Umar (African Journal of Stability and Development (AJSD), 2018)
In order to protect and preserve Islamic tenets against the British Christian Missionary Education System, the slogan, Boko-Haram, which means Western education is unlawful was developed to discourage the populace in the north from missionary education in the early stage of colonialism. This was later to be used in the modern day to describe the extreme Islamic Movement known as Jama’atu Ahli Sunnah Liddawati Wal Jihad, popularly known as Boko-Haram (Paden 2012: 41). The sect first emerged in North-East Nigeria in 2003 and from 2009 onward; their activities have claimed thousands of lives in Yobe, Borno, Adamawa, Bauchi, Abuja, Kano and Kogi States. Churches, mosques, markets, government and tertiary institutions were targeted for destruction. The people of Ebira Tao, in Kogi State, in the North Central area of Nigeria, were gripped fear because of speculation that the deadly Islamic sect has sympathizers in the community. Hence, some Ebira Tao Muslim youths were arrested by law enforcement agents on the suspicion of being adherents of the new radical Islamic ideology. Prior to this assertion, Ebiraland was noted for volatility where political and religious conflicts permeated every segment of the land. In view of this, Nigerian security personnel became suspicious and sceptical of the religious zealousness of the Ebira youths and tended to characterise it falsely. The killing of a soldier, bombing of a church, murder of a church pastor and personalities in Ebiraland with methods similar to Boko Haram modus operandi gave weight to the opinion that elements of Boko-Haram existed in Ebiraland. The paper therefore seeks to interrogate the alleged links of the Boko Haram insurgency to activities of youths in Ebiraland.